Sistem scaning barcode dan scaning QR code pada daftar kunjungan Perpustakaan Sekolah Tinggi Ilmu Ekonomi Indonesia - Siti Masruroh (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
The purpose of this study was to find out how the information system has been applied to the list of visits to the STIE Indonesia Library. The method used in this research is using qualitative research methods, with data collection through interviews, observation, and literature study. The results of this study indicate that the information system used on the list of visits to the STIE Indonesia Library has undergone several system phases, including the manual system, the data entry system in the automation system, the barcode scanning system, and the QR Code system used so far. The QR code system is considered the most effective system used on the current library visit list, because the QR Code system for users only scans barcodes available with smartphone media owned by each user, so that the difficulty in reading barcodes is minimal, which previously existed on the constraints on the barcode scanning system.